2003
DOI: 10.1021/ma021108x
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Poly(3,4-propylenedioxypyrrole)s:  High Gap and Low Redox Potential Switching Electroactive and Electrochromic Polymers

Abstract: A series of electrochromic N-substituted poly(3,4-propylenedioxypyrrole)s (PProDOPs) are reported, which exhibit the combined properties of a high (>3 eV) electronic band gap, colored oxidatively doped forms, and easily accessible, low redox potentials. Utilizing methyl (Me), propyl (Pr), octyl (Oct), propanesulfonated (PrS), and ethoxyethoxyethanol (Gly) pendants, the absorbance of the π−π* transition of the resulting polymers is blue-shifted when compared to the nonderivatized parent. For example, in the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 60 publications
10
131
0
Order By: Relevance
“…The pseudo-first-order kinetic plot for the RAFT polymerization showed a deviated trend which has obvious difference from the first-order kinetics ( Figure 2). From the downward curvature, we observed that the concentration of propagating radicals was decreasing [39]. Similar deviation has been reported for the RAFT polymerization of N-acryloylmorpholine [40], N,Ndimethylacrylamide [41] and sodium 6-acrylamidohexanoate [42] from the first-order kinetics.…”
Section: Raft Polymerization Of Te-aa In Dioxanesupporting
confidence: 85%
“…The pseudo-first-order kinetic plot for the RAFT polymerization showed a deviated trend which has obvious difference from the first-order kinetics ( Figure 2). From the downward curvature, we observed that the concentration of propagating radicals was decreasing [39]. Similar deviation has been reported for the RAFT polymerization of N-acryloylmorpholine [40], N,Ndimethylacrylamide [41] and sodium 6-acrylamidohexanoate [42] from the first-order kinetics.…”
Section: Raft Polymerization Of Te-aa In Dioxanesupporting
confidence: 85%
“…Table 1 illustrates the various structure-property relationships of the monomers from Scheme 2 and their respective polymers. It can be seen that the monomer oxidation potential (E p,m ) of most of the N-hydro monomers [35,37] is found between 0.95-1.20 V versus SCE (one notable exception is DMOP, with an E p,m of 0.84 V [32,43] ), whereas the N-alkylated derivatives [32,44] possess a monomer oxidation potential that is almost 200 mV lower. This phenomenon can be attributed to the N-alkyl group donating electron density into the p-system, raising the HOMO with respect to its N-hydro derivative.…”
Section: Pxdop Synthesismentioning
confidence: 99%
“…Linear relationships between scan rates and current intensities showed that all polymers were well adhered on ITO surface and the electrochemical processes were not limited by diffusion control [58]. A neutral state absorption maximum for P2 was recorded as 560 nm.…”
Section: Electropolymerization Of (M3)mentioning
confidence: 91%